The effect of a learning approach based on experience and prior knowledge on the mastery of the concept of static fluids - Nadrah Nadrah (Jurnal Konseling dan Pendidikan, 2022)
The development of science and technology in the world of education today has dominated the development of other sciences. Science is the study of natural phenomena. These natural phenomena can occur at any time without being realized by humans. This study aims to determine the difference in concept mastery between students who are taught with an experiential learning approach and students who are taught using a conventional approach to class XI Science at SMA Negeri 2 Makassar in the 2020/2021 academic year, to determine the differences in conceptual mastery between students who have high and low initial knowledge. This research is a type of quasi-experimental research (quasi-experimental), involving two groups, namely the experimental group and the control gro up. The data analysis carried out is descriptive and inferential analysis to examine the proposed hypothesis. The conclusion of this study is that there are significant differences in concept mastery between students who are taught using an experiential learning approach (PBP), there are significant differences in conceptual mastery among students who have high prior knowledge and there is an interaction between the learning approach and prior knowledge of mastery of students' physics concepts.